La production participative d’idées : quels effets du dispositif socio-technique sur les pratiques ? - Damien Renard (Communiquer)
The elaboration of creative solutions by the crowd has been integrated seemingly by organizations. Even if they have been using competitive models to generate creative ideas for a long time, a new model for crowdsourcing, mixing competition and cooperation, is emerging. This research aims to investigate how a coopetitive model can impact the creative process. An empirical study of 9951 individuals using a crowdsourcing platform of ideas classifies users according to their activities. A variety of roles (competitor, coopetitor, and supporter) coexist in crowd-based coopetition. We observed that, while people from the coopetitive with conflicting or complementary goals play a central role in the creative process, the crowd activity is limited to evaluating the most creative ideas.